2015
DOI: 10.1038/ki.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for loss of residual renal function in children treated with chronic peritoneal dialysis

Abstract: In dialyzed patients, preservation of residual renal function is associated with better survival, lower morbidity, and greater quality of life. To analyze the evolution of residual diuresis over time, we prospectively monitored urine output in 401 pediatric patients in the global IPPN registry who commenced peritoneal dialysis (PD) with significant residual renal function. Associations of patient characteristics and time-variant covariates with daily urine output and the risk of developing oligoanuria (under 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 42 publications
(47 reference statements)
1
15
2
2
Order By: Relevance
“…Moreover, there is a growing concern about faster decline of RRF by icodextrin-induced higher ultrafiltration compared to glucose solution. 11 , 15 , 40 Our randomized controlled study addressed this issue and clearly demonstrated that icodextrin solution preserves RRF better than glucose solutions. This finding is unlikely to be explained by escalation of high concentration glucose solution or the use of diuretics because glucose exposure did not change in the control group throughout the study and the use of medications that could potentially affect urine volume was comparable between groups.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, there is a growing concern about faster decline of RRF by icodextrin-induced higher ultrafiltration compared to glucose solution. 11 , 15 , 40 Our randomized controlled study addressed this issue and clearly demonstrated that icodextrin solution preserves RRF better than glucose solutions. This finding is unlikely to be explained by escalation of high concentration glucose solution or the use of diuretics because glucose exposure did not change in the control group throughout the study and the use of medications that could potentially affect urine volume was comparable between groups.…”
Section: Discussionmentioning
confidence: 88%
“…139 Evidence suggests that PD is associated with better preservation of residual kidney function compared with HD, typical reported rates of loss in clearance per month being 0.25-0.28 and 0.30-0.40 ml/min per 1.73 m 2 , respectively [141][142][143][144][145][146] ; the mechanism is still debated but is likely to be in part the avoidance of intravascular volume depletion which occurs more frequently with HD. 145,146,148,149 The most studied intervention to maintain residual kidney function is the use of biocompatible solutions. 145,146,148,149 The most studied intervention to maintain residual kidney function is the use of biocompatible solutions.…”
Section: Residual Kidney Functionmentioning
confidence: 99%
“…International collaborative research approaches have shown an enormous potential to identify and characterize specific aspects of paediatric kidney disease and to generate an observational evidence base for clinical recommendations. This includes studies on estimating times to ESKD in children with chronic kidney disease [97], cardiovascular consequences of chronic kidney disease in childhood [98, 99] and courses of paediatric dialysis [100]. A more recent study, ARegPKD, is dedicated to describe the details of clinical courses of patients suffering from ARPKD [101, 102].…”
Section: Future Perspectivesmentioning
confidence: 99%